Primitive Neuroectodermal Tumour of the Maxilla Sinistra Region - Maryam Fathima; Sri Mutya Sekarutami (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2019)
Primitive neuroectodermal tumors (PNET) are a group of malignant tumors composed of small round cells of neuroectodermal origin that affect soft tissue and bone. PNET have a rare incidence, occurring usualy in children and adolescents, rarely in adults. In this case report are focus of Peripheral primitive neuroektodermal tumors. Peripheral primitive neuroectodermal tumors (PNETp) are a group of aggressive malignancies that most commonly present in multiple tissues and organs including kidney, adrenal, bladder, liver, small intestine, colon and rectum, with a preferred location within the chest area (thoracopulmonary region), in the limbs and around the spine, but rarely, in the head and neck area. Here we present a case of the maxilla sinistra PNETp in a 17-year-old girl and we discuss the clinical features, histopathological characteristics, diagnosis, and treatment.